(untitled) (Cardiovascular Journal, 2021)
Background: This echocardiographic study was undertaken to establish incidence, pattern & complications in patients of valvular heart disease. Methods: A total of 97 patients were enrolled among the patients attended in echo lab at Ibrahim cardiac hospital & Research Institute over a period of 1 year. Results: Mean age was 53.8±1.5 years. Male were predominant (58.76% vs 41.23%). Most common symptom was shortness of breath (60.8%) followed by palpitation (43.3%). 39.2% of patients had normal ECG & 12.4% revealed AF. The most common complication was pulmonary hypertension (54.6%) followed by pulmonary edema (26.8%), Stroke (10.3%), Left atrial thrombus (7.3%), & infective endocarditis (6.2%). MV was most commonly involved (72.2%) followed by aortic valve (AV) (66.0%), tricuspid valve (TV) (54.6%) & pulmonary valve (PV) was (20.6%). Rheumatic involvement (52.6%) constituted the dominant cause than degenerative & congenital (24.7% in each). Mitral stenosis (MS) was predominant (52.6%) & was rheumatic in origin; then aortic stenosis (AS) (48.5%) which was mostly degenerative followed by bicuspid aortic valve (8.2%). Mitral regurgitation (MR) was the most common valvular lesion (64.9%); then aortic regurgitation (AR) (51.5%) which was also rheumatic in etiology. Multiple valve involvement was also present. The most common variety was MS+MR (43.3%). Tricuspid stenosis (TS) was in association with MR+AR (1.03%). Tricuspid regurgitation (TR) was 58.8%, mostly secondary to rheumatic involvement of other valves. Severe TR (5.2%) was due to Ebstain anomaly and prolapse (4.1% & 3.1%). ventricular systolic & diastolic functions were normal mostly. Conclusion: Among the rheumatic heart disease patients’ mitral valve was the most commonly affected valve. Mitral regurgitation was the most common valvular lesion. Rheumatic involvement remains the dominant cause of valvular heart disease in Bangladesh. Cardiovasc. j. 2021; 13(2): 144-153